Bimetallic uranium complexes with 2,6-dipicolinoylbis(N,N-dialkylthioureas) - Njiki Noufele, Christelle; Schulze, Dennis; Roca Jungfer, Maximilian; Hagenbach, Adelheid; Abram, Ulrich (Molecules, 2024)
2,6-Dipicolinoylbis(N,N-dialkylthioureas), H2LR, readily react with uranyl salts under formation of monomeric or dimeric complexes of the compositions [UO2(LR)(solv)] (solv = donor solvents such as H2O, MeOH or DMF) or [{UO2(LR)(µ-OMe)}2]2− (1). In such complexes, the uranyl ions are exclusively coordinated by the “hard” O,N,O or N,N,N donor atom sets of the central ligand unit and the lateral sulfur donor atoms do not participate in the coordination. Different conformations have been found for the dimeric anions. The bridging methanolato ligands and the four uncoordinated sulfur atoms can adopt different orientations with respect to the equatorial coordination spheres of the uranyl units. The presence of non-coordinated sulfur atoms offers the opportunity for the coordination of additional, preferably “soft” metal ions. Thus, reactions with [AuCl(PPh3)], lead acetate or acetates of transition metal ions such as Ni2+, Co2+, Fe2+, Mn2+, Zn2+, or Cd2+, were considered for the syntheses of bimetallic complexes. Various oligometallic complexes with uranyl units were prepared: [{UO2(LR)(μ-OMe)(Au(PPh3)}2] (2), [(UO2)3Pb2(LR)4(MeOH)2(μ-OMe)2] (3), [M{UO2(LR)(OAc)}2] (M= Zn, Ni, Co, Fe, Mn or Cd) (R = Et: 5, RR = morph: 6), or [(UO2)(NiI)2(LR)2] (7). The products were extensively studied spectroscopically and by X-ray diffraction.